Geopolymeric concretes based on fly ash with high unburned content (2018)
This study used fly ash (FA) with a high amount of unburned content (21%) to produce simple (Geo FA) and binary (Geo FA/granulated blast furnace slag [GBFS]) geopolymeric concretes. The effect on the mechanical strength of the SiO2/Al2O3 and Na2O/SiO2 molar ratios and the percentage of GBFS (% GBFS) added to the blend were determined. Using the optimal parameters of alkaline activation, concretes with strengths up to 48 MPa were obtained after 28 days of curing at room temperature (25 °C). The results of this study are complemented by the microstructural characterisation of the geopolymeric pastes using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) techniques